Assessment of Physico-Chemical and Biological Factors in Relation to Productivity Potential of A Fresh Water Bodies Of Bhikhanpura, Muzaffarpur (Bihar) - Medha Kumari,; Faiyaz Ahmad, (International Journal of Scientific Research in Science and Technology, 2025)
Water quality is a key factor that affects harvest outcome from fresh water body. Irregular or a periodic variations of different water quality variables can influence the growth, survival, and yield of aquatic livestock in the ponds. The basic understanding of the limnology, productive potentials and fish production of water body is essential for the sustainable development at Bhikhanpura in Muzaffarpur. The area of  Bhikhanpura is 24-hectare having depths of about 3.5m. An investigation was conducted on the ecology of productivity, plankton, and macrophytes. The transparency value was low during summer and the pH was slightly alkaline. The monthly mean values of dissolved oxygen were somewhat lower in this closed water body. The nitrate values were higher in summer and lower during the monsoon period. Among the plankton, community, phytoplankton formed the main portion of the total plankton. Cyanophycean was the major contributor among the phytoplankton as Chlorophyceae was the second largest group. The monthly mean value of the zooplankton population was 417.20µl-1 in Bhikhanpura. The water body contain a   mixed population of macrophytes with the dominance of submerged plants throughout the year. Fish production was recorded at 1158.80 kg/ha/yr. However, the production of carps was much higher than the miscellaneous fishes.
Keywords: Water Quality; Bhikhanpura; Productivity; Plankton; Macrohytes; Zooplankton